An umbrella review of systematic reviews/meta-analyses evaluating the antimicrobial activity of various nanoparticles on orthodontic materials & components - Vaibhav Kumar; Ruchira Shreevats; Aysha Syed; Mansi Jaiswal; Meghna Vandekar (Journal of Oral Biology and Craniofacial Research)
Introduction: White spot lesions (WSLs) are a prevalent issue during fixed orthodontic treatment. Orthodontic materials, such as wires, brackets, and adhesives, often create an environment that promotes microbial growth, particularly from acidogenic bacteria like Streptococcus mutans, leading to enamel demineralization. Traditional preventive measures include fluoride treatments and meticulous oral hygiene, but integrating antimicrobial nanoparticles into orthodontic materials offers a promising alternative. This umbrella review evaluates the antimicrobial efficacy of nanoparticles incorporated into orthodontic materials by assessing evidence from systematic reviews and meta-analyses. Various nanoparticles, including ZnO, Ag, and TiO2, were studied for their potential to reduce microbial colony formation and adherence to orthodontic materials. Materials and method: A literature search was conducted across PubMed, Google Scholar, The Cochrane Library, and LILACS, yielding one hundred and sixty-seven articles after removing duplicates. Following abstract and title screening, twenty-seven studies were selected for full-text review, and nine were included in the qualitative analysis. This review adheres to PRISMA guidelines and is registered with PROSPERO (CXXXXXXXXXXXX2). Results: The studies indicate that incorporating AgNP into orthodontic adhesives enhances antimicrobial activity but exhibits high heterogeneity, necessitating more in vivo studies. TiO2-coated brackets show antimicrobial properties against various pathogens. Nanoparticle-coated archwires with AgNP, N-doped TiO2, graphene oxide, and zinc oxide reduce demineralization, are biocompatible, and reduce surface roughness, showing good to fair antimicrobial activity. Results should be interpreted cautiously, and further clinical and long-term studies are required to confirm the effectiveness of these nanoparticles in preventing white spot lesions.